Design and Development of a Golf Ball Cleaning Machine at UTHM Driving Range - Bin Shahrizan, Mohamad Syahin Aiman; Bin Hassan, Mohd Fahrul (Research Progress in Mechanical and Manufacturing Engineering, 2024)
A golf ball cleaning machine is a machine that can remove dirt that appear on the golf ball by using brush in a spiral. The goals are to identify parameter for cleaning the golf ball using engineering design approach. Other than that, to design a golf ball cleaning machine based on conceptual design process. Lastly, to fabricate the golf ball cleaning machine for proof-of-concept testing. In order to achieve the goals, the scope and limitation need to be set which are the first one is the place of the driving range is at UTHM Driving Range, the type of balls that are involves are the practice ball, and lastly focus on small category of driving range facility. Methods that are being used are by using the flow chart to structure the whole process to solve the problem. Then by stating up the problem identification, i was able to make a concept generation by using morphological chart. The morphological contain three alternative which can select to get a perfect combination. Then by concept evaluation, it entails a methodical approach to examining and analyzing the conceived ideas or concepts to ascertain their practicality, feasibility, and likelihood of success. After that, the concept will be selected at the concept selection. At the product architecture, the product modules will be set by using schematic diagram, cluster diagram, and incidentals interaction. Then, the modelling and simulation are done by using Solidworks 2023 and the simulation that are being used are the static analysis and the buckling analysis. In conclusion, I managed to to learn on how to design and develop using engineering approach and getting used to it. This project will able to solve the cleaning problem at the UTHM driving range.